Successful treatment of malakoplakia of the bladder in a kitten. Issue 8 (August 2013) - Rutland, Bronwyn E; Nimmo, Judith; Goldsworthy, Matthew; Simcock, James O; Simpson, Kenneth W; Kuntz, Charles A
A 4-month-old female kitten presented with chronic lower urinary tract signs and Escherichia coli cystitis, and was diagnosed with urinary bladder malakoplakia based upon histopathology. The kitten was treated with a prolonged antibiotic course and the malakoplakia resolved. Malakoplakia is a chronic granulomatous reaction characterized by the formation of Michaelis–Gutman bodies within von Hansemann macrophages. It is well described in humans, but has never been documented in a living veterinary patient. This case report describes the first successful treatment of malakoplakia in veterinary medicine.